The Social Construction of the Meaning of Beauty in Dove and Wardah Advertisements on YouTube - Pia Khoirotun Nisa; Jamhari Makruf; Zakaria Zakaria; Misnan Misnan (ETTISAL : Journal of Communication, 2025)
This study aims to analyze how Dove and Wardah’s digital campaigns on YouTube shape and deconstruct conventional beauty narratives through Peter L. Berger and Thomas Luckmann’s social construction theory. A qualitative approach combining critical discourse analysis and in-depth interviews was applied to explore audience interpretations of both campaigns. The findings reveal that Wardah successfully contextualizes beauty messages within religious and cultural frameworks by emphasizing values such as modesty, spirituality, and inner beauty, which strongly resonate with Indonesian Muslim women. In contrast, Dove focuses on global inclusivity through narratives of body and age diversity, but its secular orientation often limits cultural relevance in the Indonesian context. The study also identifies a gap between the inclusivity messages promoted by the brands and the audience’s interpretations. Some audiences accept the messages, while others resist or modify them according to their social and cultural values. Analysis of YouTube interactions—comments, likes, and shares demonstrates that audiences act as active meaning-makers rather than passive consumers. Through the processes of externalization, objectivation, and internalization, a new social reality of beauty emerges, redefining beauty as a synthesis of spirituality, diversity, and authenticity beyond mere physical appearance.